Palm Oil Import Demand in North America Countries - Tandra, Hansen; Suroso, Arif Imam; Syaukat, Yusman; Najib, Mukhamad (Jurnal Manajemen & Agribisnis, 2022)
Palm oil is one of the agricultural commodities grown in world trade. North America is one of the regions with high import demand, so that the region can be observed as an export destination. This study aimed to examine the palm import demand in three selected North American Countries (United States of America (USA), Canada and Mexico) and its determinants. Autoregressive Distributive Lags (ARDL) was applied in this study between 1990 and 2017. The results indicate that the demand for palm oil in North American countries has increased. However, the import growth and shares have fluctuated relatively. GDP, GDP Indonesia, GDP Malaysia world palm oil prices, soybean oil prices, and biodiesel production significantly affect palm oil imports in the USA in the long and short-run. The GDP and GDP of Indonesia are the factors that influence palm oil import in Canada and Mexico in the long run. However, we found the impact of GDP Malaysia and GDP Indonesia in Canada in the short-run. Moreover, Indonesia's GDP and GDP significantly influenced palm oil import in Mexico. This research implies that oil palm exporting countries need to consider these factors, especially GDP, before expanding their market to North American countries as one of the biggest palm oil markets in the global world. Keywords: business analytics, biofuel, gdp, import, palm oil, price, north america